Electrochemical Condensation of Methylviologen on Specifically‐adsorbed Anion Layers. Issue 6 (5th April 2019) - Tsuruta, Keisuke; Haraguchi, Ryusei; Nishiyama, Katsuhiko; Sawaguchi, Takahiro; Yoshimoto, Soichiro
Abstract: The adsorption of methylviologen dications (MV 2+ ) on single‐crystalline Au electrodes in both H2 SO4 and HClO4 was examined. MV 2+ strongly interacted with sulfate and bisulfate anions adsorbed on the Au(111) electrode surface in 0.05 M H2 SO4 under a controlled potential of 1.25 V vs. the reversible hydrogen electrode (RHE). A characteristic non‐Faradaic current was observed at 1.10 V vs. RHE. When adsorption of MV 2+ was carried out in 0.1 M HClO4, the electrochemical response of MV 2+ was less than that obtained in H2 SO4 . The results show that the formation of a highly ordered sulfate/bisulfate adlayer plays an important role in the formation of condensed MV 2+ layers. Examination of polycrystalline Au and Au(100) electrodes revealed a poor electrochemical response due to the surface roughness of the Au substrate, but the electrochemical detection was applicable to polycrystalline Au electrodes. A systematic investigation of the structural dependency of viologen derivatives showed that molecular size is important for electrostatic interactions with a highly ordered sulfate/bisulfate adlayer. The findings of the present study demonstrate successful detection of MV 2+ at a concentration of ≤1 pM with a non‐Faradaic current. Abstract :